WALK & TALK: EMERGING QUALITATIVE RESEARCH METHODS IN SOCIOLOGY - Ramchandra Baral (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
This study examines the Walk & Talk method as an innovative approach to qualitative research, emphasizing its ability to capture rich, contextually grounded data through mobility and embodied experiences. By integrating walking interviews into fieldwork in Nepal, the method enhances data collection via seeding, feeding, and bridging processes. These processes facilitate reflective dialogue (seeding), provide deeper insights through physical engagement (feeding), and connect individual narratives to broader social and cultural contexts (bridging). The study illustrates how the Walk & Talk method shifts from inductive to abductive reasoning, uncovering new insights and theoretical connections in real-time. Fieldwork on spiritual practices, social relations, tourism management, and climate change adaptation demonstrates the method's effectiveness in exploring the intersections of place, identity, and social dynamics. The study highlights the method's potential for interdisciplinary applications in social anthropology, cultural sociology, and environmental studies, expanding qualitative research methodologies to explore intersectional identities and community resilience across diverse contexts.